2005
DOI: 10.1021/cm051058l
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Transmission Holographic Gratings via Different Polymerization Rates of Dipentaerythritol Acrylates and Siloxane-Containing Epoxides

Abstract: Well-defined transmission holographic gratings with high diffraction efficiency were fabricated by irradiating a mixture of photopolymerizable materials with different reaction rates consisting of penta-/ hexafunctional acrylates and siloxane-containing glycidyl ether (88%) or cyclohexene oxide (85%) as radically and cationically polymerizable monomers, respectively, with Nd:YAG laser (λ ) 532 nm). The ratio between the acrylate and epoxide was important to obtain gratings with high diffraction efficiency. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…[8] Epoxides are used as cationically polymerizable monomer to obtain high performance in terms of inducible refractive index contrast, [4] energetic sensitivity [19] as well as mechanical stability. [20] With the aim of optimization, we consider possibilities to further reduce undesired volumetric deformations. To achieve this, a deeper understanding of the basic principles involved in volume changes is required.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Epoxides are used as cationically polymerizable monomer to obtain high performance in terms of inducible refractive index contrast, [4] energetic sensitivity [19] as well as mechanical stability. [20] With the aim of optimization, we consider possibilities to further reduce undesired volumetric deformations. To achieve this, a deeper understanding of the basic principles involved in volume changes is required.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Grating Fabrication: Holographic gratings were fabricated by preferential formation of photoproducts in the region of constructive interference arising from the overlap of object and reference laser beams. [20,21] The cell was constructed by sandwiching the prepolymer mixtures between two ITO-coated glass plates with gaps of 4.2-11 mm, adjusted by bead spacers. The prepolymer mixtures were irradiated with an Ar-ion laser (514 nm) at 90 mW cm À2 with exposure times of 8 min.…”
Section: Methodsmentioning
confidence: 99%
“…We reported the influence of siloxane bonds on the viscosity of the compounds, and indicated the importance of low viscosity of siloxane-containing compound in fabrication of gratings with high diffraction efficiency. 28 SEM morphology of the grating was shown in Figure 6. In SEM picture of the ethanol-washed sample in Figure 6, it was observed that the siloxane-containing 11OS3CB well phase-separated from the polymer matrix.…”
Section: Superiority Of Liquid Crystals With Siloxane Spacer Over Thomentioning
confidence: 99%